How luck happens : using the science of luck to transform life, love, and work - Kaplan, Janice; Marsh, Barnaby (Dutton, 2018)
"New York Times bestselling author Janice Kaplan examines the phenomenon of luck--and discovers the exciting ways you can boost your chances and set yourself up to get lucky in everyday life. After spending a year researching and experiencing gratitude for The Gratitude Diaries, Janice Kaplan is back to tackle another big, mysterious influence in all our lives: luck. And this time she's joined on her journey by coauthor Dr. Barnaby Marsh, a renowned academic who guides her exploration. Together they look at the factors that led a young struggling Harrison Ford to a chance encounter with fledgling director George Lucas, and they find out what distinguishes luck from pure randomness. They discover that much of what we call luck is really under our control, and they reveal the simple techniques to create luck in love and marriage, business and career, health, happiness, and family relationships. Using original research and fascinating studies, they offer breakthrough insights on how all of us--from CEOs to stay-at-home moms--can tip the scales of fortune in our favor. Through a mix of scientific research, interviews with famous and successful people, and powerful narrative, How Luck Happens uncovers a fascinating subject in accessible and entertaining style"--